Covalent organic polymer induces apoptosis of liver cancer cells via photodynamic and photothermal effects - Xu, Wenze; Zhang, Mengfan; Wang, Wenhui; Wang, Manzhou; Li, Bingjie; Li, Hao; Kuang, Donglin; Liang, Chao; Ren, Jianzhuang; Duan, Xuhua (Frontiers in Oncology, 2022)
The purpose of this study was to explore the photodynamic and photothermal effects of the supramolecular material Purp@COP and to test the anti-cancer effect on HepG2 cells in vitro. Materials and Methods Purp@COP is a covalent organic polymer (COP) with robust tailoring heteroatom incorporation, plentiful pore structure, and multi-function similar to metal-organic framework (MOF).Hepatocellular carcinoma cell line HepG2 was cultured with Purp@COP for 24 h and treated with near-infrared 808 nm laser 1W/cm2 for 10 min. CCK-8 assay, colony formation assay, live-dead cell fluorescence staining and Annexin-V/PI staining flow cytometry were performed to detect the viability, proliferation and apoptosis of the HepG2 cells. Results The supramolecular material Purp@COP exhibited significant photothermal performance under near-infrared 808 nm laser irradiation in vitro. With the treatment of Purp@COP and near-infrared 808 nm laser irradiation on HepG2 cells, cell viability and colony formation capacity were decreased, and the number and proportion of apoptotic cells was increased. Conclusions The supramolecular material Purp@COP has both photothermal and photodynamic effects and can significantly induce cancer cell death and inhibit the proliferation of cancer cells in vitro.